Research progress of clinical intervention for apnea in extremely and very preterm infants (极早和超早产儿呼吸暂停临床干预方法进展) - LU Lijun (陆丽君); FENG Xuemo (冯雪茉); LU Yunhong (卢运红) (中西医结合护理)
Neonatal apnea is more common in extremely or very preterm infants. Influenced by a variety of comprehensive factors such as hypoplasia of receptors, electrolyte disorder, bacterial and viral infection, it is easy to lead to cerebral ischemia and hypoxia and other complications in neonates, which is the main cause of neonatal death. By using the method of literature review, induction and comparison, this paper made an analysis of clinic interventions for apnea in extremely and very preterm infants, and provided a basis for further effective intervention. (新生儿呼吸暂停多见于极早产儿或超早产儿, 受感受器发育不全、电解质紊乱、细菌病毒感染等多种因素的影响, 容易导致新生儿出现大脑缺血缺氧等并发症, 是造成新生儿死亡的主要原因。本文通过分析、归纳、比较极早产儿及超早产儿呼吸暂停临床干预方法, 以期为进一步开展有效干预提供依据。)